The Effectiveness of The Role of The Land Office (Badan Pertanahan Nasional) as A Mediator in Resolving Land Disputes - Basyarudin (Faculty of Law, Universitas Pekalongan, 2025)
Land is an object that is vulnerable to disputes and problems regarding ownership and boundaries. The problem raised in this research concerns the effectiveness of the mediation role of the national land agency in resolving land conflicts and the factors that influence it. Research Objective: To examine and analyze the effectiveness of the role of the Land Office in resolving land disputes which are carried out by the provisions and are binding according to statutory regulations. This research was carried out in a normative juridical manner using a statutory approach. The role of the Land Office or National Land Agency as an effective mediator in resolving land disputes as a government institution that carries out government duties in the land sector. The role of the Land Office as a mediator in resolving land disputes is to strive to be a means of resolving land disputes by implementing a legal system that guarantees justice, legitimacy, and legal certainty. Therefore, it can be concluded that the results of conciliation within the land agency can have binding legal value, which indirectly shows that the role of the land agency as a mediator in resolving land disputes has been effective, but in reality, very few land disputes have been successfully resolved